A retrospect on the dust-laden history : the past and present of Tekong Island in Singapore - Chen, Poh Seng (World Scientific, 2012)
Chen Poh Seng's great grandfather lived in Pulau Tekong, his 50-over cousins were born and educated there. He lived in Changi Point which is 30 minutes away by ferry. Lee Leong Sze is a Malaysian, graduated from the Department of History, National Chong Hsing University, Taiwan, obtained PhD in Singapore. Two researchers met in August 2005. They shared the same interest in studying the history of Pulau Tekong. During the study, they had full support and encouragement from former residents. The book describes how Pulau Tekong Island developed during the early 20th century. It describes where th.